Lewy pathology in Parkinson's disease consists of crowded organelles and lipid membranes - Shahmoradian, Sarah H; Lewis, Amanda J; Genoud, Christel; Hench, Jürgen; Moors, Tim E; Navarro, Paula P; Castaño-Díez, Daniel; Schweighauser, Gabriel; Graff-Meyer, Alexandra; Goldie, Kenneth N; Sütterlin, Rosmarie; Huisman, Evelien; et al. (Nature neuroscience, 2019)
Parkinson's disease, the most common age-related movement disorder, is a progressive neurodegenerative disease with unclear etiology. Key neuropathological hallmarks are Lewy bodies and Lewy neurites: neuronal inclusions immunopositive for the protein α-synuclein. In-depth ultrastructural analysis of Lewy pathology is crucial to understanding pathogenesis of this disease. Using correlative light and electron microscopy and tomography on postmortem human brain tissue from Parkinson's disease brain donors, we identified α-synuclein immunopositive Lewy pathology and show a crowded environment of membranes therein, including vesicular structures and dysmorphic organelles. Filaments interspersed between the membranes and organelles were identifiable in many but not all α-synuclein inclusions. Crowding of organellar components was confirmed by stimulated emission depletion (STED)-based super-resolution microscopy, and high lipid content within α-synuclein immunopositive inclusions was corroborated by confocal imaging, Fourier-transform coherent anti-Stokes Raman scattering infrared imaging and lipidomics. Applying such correlative high-resolution imaging and biophysical approaches, we discovered an aggregated protein-lipid compartmentalization not previously described in the Parkinsons' disease brain.